589 Physical demands of fire fighting for seafarers-an emerging aspect of occupational safety in seafaring. (1st September 2016) - Visuri, Susanna; Miilunpalo, Paivi; Lindholm, Harri; Lusa, Sirpa; Rauttola, Ari-Pekka; Pylkkonen, Mia
Abstract : Background: All seafarers with designated emergency tasks must take part to a basic safety training including a course of basic fire fighting despite their physical fitness. Physical fitness of seafarers is often unsatisfactory, obesity and ageing impair it even further. There is not much information about the physical strain of the courses' exercises for seafarers. Therefore the aim of the study was to measure physical strain of seafarers during a fire fighting course. Methods: Fourteen male master mariner students aged 19–21 attended to a simulated smoke-diving drill with self-contained breathing apparatus (SCBA). Perceived exertion was assessed by Borg scale and energetic strain was assessed by estimating oxygen consumption indirectly with heart rate variability method. Students conducted two exercises in pairs with SCBA. In the first exercise, each pair walked through warm, smoke filled enclosed spaces. The second exercise started with a fire attack and continued by searching and rescuing a victim (a doll, weight 30 kg). Results: The first exercise lasted on average 14 minutes. During the exercise, the highest heart rate (HR) level was on average 145 (123–169) b/min and the maximum oxygen intake (VO2 max) 34 (25–42) ml/min/kg. The physical load was 7 (3–10) MET and perceived exertion on average was 11 (7–15). The second exercise lasted on average 12 minutes. The highest HR level was on average 167 (126–181) b/min and VO2 max was 40 (27–49) ml/min/kg. The physical load of exercise was 10 (6–12) MET and the perceived exertion on average was 13 (9–15). Conclusions: Seafarers' safe performance during basic fire fighting course requires aerobic fitness equivalent to extremely vigorous intensity activities (like running stairs up). The real-life smoke-diving duties on ship have been reported to be even more strainful. For the safety of seafarers, both promotion of physical fitness and regular training of emergency duties should be seen as an occupational safety issue.